2011
DOI: 10.1007/s13197-011-0445-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and in vitro probiotic evaluation of lactic acid bacteria isolated from idli batter

Abstract: An Indian traditional fermented food, idli batter, was used as a source for isolation of lactic acid bacteria (LAB). A total of 15 LAB strains were isolated on the basis of their Gram nature and catalase activity. Of these, one lactobacilli strain and one lactococci strain which showed antimicrobial activity were identified using biochemical characterization, sugar utilization and molecular sequencing. The microbes, labeled as IB-1 (Lactobacillus plantarum) and IB-2 (Lactococcus lactis) were tested for their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 31 publications
(24 reference statements)
0
19
0
1
Order By: Relevance
“…The Lactobacillus isolates in this study showed antagonistic potential toward almost all of the pathogenic bacteria; however, they did not significantly inhibit the growth of Y. enterocolitica. Simsek et al (2006) and Iyer et al (2013) conducted a similar study and reported the antibacterial activity of lactobacilli isolated from fermented products against various Gram positive and negative pathogens. Lactobacillus isolates (L1, L11, L14 and L19) having antimicrobial activity may be effectively used in various food products to prevent pathogenic bacterial contamination that may occur during the manufacturing processes and transportation.…”
Section: Discussionmentioning
confidence: 94%
“…The Lactobacillus isolates in this study showed antagonistic potential toward almost all of the pathogenic bacteria; however, they did not significantly inhibit the growth of Y. enterocolitica. Simsek et al (2006) and Iyer et al (2013) conducted a similar study and reported the antibacterial activity of lactobacilli isolated from fermented products against various Gram positive and negative pathogens. Lactobacillus isolates (L1, L11, L14 and L19) having antimicrobial activity may be effectively used in various food products to prevent pathogenic bacterial contamination that may occur during the manufacturing processes and transportation.…”
Section: Discussionmentioning
confidence: 94%
“…The topography is mostly mountainous and covered with the Himalayas which favor different habitats and microflora of beneficial use. In recent times, extensive research has been carried out on isolation and screening of microbes from traditional fermented foods due to their eco-friendly and genetically sturdy nature (Iyer et al, 2013). In addition, soybean meal is an important protein source in animal feed (Opazo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are live microbial supplements which if taken in adequate amounts (Lyer et al 2011) beneficially affect the host by improving its intestinal microbial balance (Krasaekoopt et al 2003). They impart therapeutic effects and promote health by preventing various diseases (Vanaja et al 2011).…”
Section: Introductionmentioning
confidence: 99%